Microencapsulação de hidrolisado de fígado suíno - Souza, Hellen Karoline Spricigo de (2023)
This research, conducted in partnership with BRF S.A., aimed to evaluate the production of pork liver hydrolysates using different enzymes and different process times. The study also aimed to investigate the effects of hydrolysis on functional, bioactive, and rheological properties, as well as to evaluate microencapsulation using “spray drying” and freeze-drying with various encapsulating materials. Pork liver was hydrolyzed using the enzymes Alcalase® 2.4L, FoodPro® PXT, Pancreatin, and Pepsin for 5 hours, and the enzymatic kinetics were evaluated during this period. The enzymes Alcalase® 2.4L and FoodPro® PXT were selected, and a new kinetics study was conducted, evaluating the times of 1 h, 4 h, 6 h, 8 h, 10 h and 12 h. The antioxidant activity of the hydrolysates was evaluated using the DPPH and ABTS methods. The effects of hydrolysis on the physicochemical properties, functional properties, antimicrobial activity, and rheological behavior of the hydrolysates produced with Alcalase® 2.4L and FoodPro® PXT at times of 1 h and 4 h time were also investigated. Regarding microencapsulation, the pork liver hydrolysate with Alcalase® 2.4L for 4 h was used along with different encapsulating materials (arabic gum, maltodextrin, whey protein, combination of whey protein with maltodextrin, xanthan gum, and soy protein isolate) and two encapsulation methods (“spray drying” and freeze-drying). The produced microcapsules were evaluated for morphology, particle diameter, water activity, FTIR spectra, thermal stability, gastrointestinal simulation, antioxidant activity and antimicrobial activity. The results showed that all the hydrolysates exhibited higher antioxidant activity compared to the fresh pork liver. In addition, low molecular weight peptides were identified in the hydrolysates, with high bioactive potential. The hydrolysates showed excellent foaming characteristics and water and fat retention capacity, but showed low emulsion stability, and the hydrolysates with the FoodPro® PXT enzyme showed low emulsion formation capacity. The hydrolysates also showed antimicrobial activity against the bacteria Staphylococcus aureus and the fungus Candida albicans. Regarding the rheological behavior, the pork liver exhibited pseudoplastic non-Newtonian fluid behavior, while the hydrolysates with Alcalase® 2.4L enzyme showed non-Newtonian behavior with thixotropic properties, and the hydrolysates with FoodPro® PXT enzyme behaved as Newtonian fluids. In microencapsulation, it was observed that the particles produced by “spray drying” exhibited a spherical shape with varying sizes (0.4 – 37.6 μm), while the particles obtained by freeze-drying displayed a morphological appearance of brittle flakes with irregular sizes (0.4 – 39.7 μm). Thermogravimetric analyzes of the microcapsules showed good thermal stability. All microcapsules showed low water activity, being considered stable from a biological and chemical point of view. In the gastrointestinal simulation, the wall materials were adequate for the protection of antioxidant biopeptides, except for xanthan gum, which showed low efficiency. As for antimicrobial activity, the microcapsules produced with Gum Arabic, Soy Protein Isolate and Whey+Malto (only those produced in a lyophilizer) showed an inhibitory action against C. albicans and the microcapsules produced with Whey Protein, Whey+Malto and Soy Protein Isolate (only those produced in “spray drying”) showed inhibition for S. aureus. The results obtained for gastrointestinal simulation demonstrated that microencapsulation preserved the antioxidant and antimicrobial activity of the pork liver hydrolyzate, confirming its importance for the maintenance of biopeptides. Thus, microencapsulated pork liver hydrolyzate has high potential for industrial-scale applications in different segments, such as food, nutraceuticals and supplements.